From metallic liquids to metallic glasses: in-situ monitoring the atomic structure evolution by synchrotron X-ray diffraction - Stiehler, Martin E.; Georgarakis, Konstantinos (Taylor & Francis, 2025)
Although ubiquitous in nature and technology, a deep understanding of glass formation and glass transition is still missing. It is assumed that the remarkable slowdown of kinetics towards vitrification can be traced back to structural changes in the undercooled liquid. Therefore, a continuous monitoring of the atomic structure during cooling from the equilibrium liquid to the glass is inevitable. However, the high critical cooling rates usually necessary for vitrification of metallic alloys make this a challenging, but at the same time very exciting, endeavor. Only in recent years, it has been technologically possible to achieve in-situ monitoring of the evolving structure for a small number of metallic-glass-forming alloys. Currently, only high-energy X-rays from synchrotron sources as probes in combination with fast two-dimensional detectors can capture diffraction images from usually containerlessly levitated samples with the necessary scattered intensity as well as resolution in space and time. Here, results for those materials where in-situ monitored vitrification has been experimentally accomplished are reviewed, and approaches to experiment and data processing are compared. Insights into the structural behaviour during vitrification derived from these experiments are discussed. Results from accompanying simulations are also included. In addition to the in-situ observation of vitrification, structural indications of possible liquid-liquid crossovers in the alloys are considered as well.
Keywords: Applied Physics; 3406 Physical chemistry; 4017 Mechanical engineering; 5104 Condensed matter physics; Glass-forming ability; glass transition; liquid-liquid transitions; synchrotron radiation; in-situ diffraction; vitrification; containerless levitation; rapid solidification